Odpowiedź :
a)
(2x -1)(3x+2) - 7x(x+1) = 6x² +4x -3x -2 -7x² -7x = -x² -6x -2
b)
(x -5)²(x -√2) + x²(2 - x√2) =(x² -10x +25)(x -√2) + 2x² -x³√2 =
= x³ - 10x² + 25x -x²√2 +10x√2 -25√2 + 2x² -x³√2 =
= (1 -√2)x³ -(8 +√2)x² +(25 +10√2)x -25√2
(2x -1)(3x+2) - 7x(x+1) = 6x² +4x -3x -2 -7x² -7x = -x² -6x -2
b)
(x -5)²(x -√2) + x²(2 - x√2) =(x² -10x +25)(x -√2) + 2x² -x³√2 =
= x³ - 10x² + 25x -x²√2 +10x√2 -25√2 + 2x² -x³√2 =
= (1 -√2)x³ -(8 +√2)x² +(25 +10√2)x -25√2
a) (2x - 1)(3x + 2) -7x(x + 1) =6x² + 4x - 3x - 2 - 7x² - 7x= -x² - 2 - 6x
b) (x -5)²(x -√2) + x²(2 - x√2) =(x² -10x +25)(x -√2) + 2x² -x³√2 =
= x³ - 10x² + 25x -x²√2 +10x√2 -25√2 + 2x² -x³√2 =
= (1 -√2)x³ -(8 +√2)x² +(25 +10√2)x -25√2
b) (x -5)²(x -√2) + x²(2 - x√2) =(x² -10x +25)(x -√2) + 2x² -x³√2 =
= x³ - 10x² + 25x -x²√2 +10x√2 -25√2 + 2x² -x³√2 =
= (1 -√2)x³ -(8 +√2)x² +(25 +10√2)x -25√2